Two new benzolactones from the leaves of Nicotiana tabacum and their anti-tobacco mosaic virus activities. Issue 13 (2nd July 2016) - Shen, Qinpeng; Xu, Xingmeng; Zhang, Fengmei; Xiang, Nengjun; He, Pei; Si, Xiaoxi; Zhu, Ruizhi; Wang, Kunmiao; Liu, Zhihua; Liu, Chunbo; Miao, Mingming
Abstract: Two new benzolactones, 5-methyl-6-prenyl-isobenzofuran-1(3 H )-one (1 ), 5-hydroxymethyl-6-prenyl-isobenzofuran-1(3 H )-one (2 ), together with four known phenolic compounds (3–6 ), were isolated from the leaves of Nicotiana tabacum . Their structures were elucidated by spectroscopic methods, including extensive 1D and 2D NMR techniques. Compounds1–6 were evaluated for their anti-tobacco mosaic virus (anti-TMV) activities. The results showed that compounds1–6 exhibited high anti-TMV activities with inhibition rates in the range of 16.9–26.2%, respectively. Abstract :